Iron deficiency anaemia: With the conclusion of a need for iron reader - Lim W.F.; Yap B.K.; Lai M.I.; Talik N.; Nasser A.A.; Al-Haiqi A.M.A.; Krishnan P.S. (Institute of Physics Publishing, 2023)
Hemoglobin; mHealth; Clinical symptoms; Cognitive development; Haemoglobins; Iron deficiency; Laboratory and field studies; Oxygen Carrier; Red blood cell; Thalassaemia; Iron